CCR2 Signal Facilitates Thymic Egress by Priming Thymocyte Responses to Sphingosine-1-Phosphate - Aili, Abudureyimujiang; Zhang, Jie; Wu, Jia; Wu, Haoming; Sun, Xiuyuan; He, Qihua; Jin, Rong; Zhang, Yu (Frontiers in Immunology, 2018)
The signal mediated by sphingosine-1-phosphate receptor 1 (S1P1) is essential but seemingly insufficient for thymic export of newly generated T cells. Here we reported the identification of CCR2 as an additional regulator of this process. CCR2 showed a markedly increased expression in the most mature subset of single-positive (SP) thymocytes. Its deficiency led to a reduction of recent thymic emigrants (RTE) in the periphery and a simultaneous accumulation of mature SP cells in the thymus. The CCR2 signaling promoted thymic emigration primarily through modulating the chemotactic responses to S1P1 engagement. On one hand, the chemokinesis induced by CCR2 activation endowed thymocytes with enhanced capacity to respond to S1P-induced migration. On the other hand, CCR2 signaling through Stat3 augmented FoxO1 activity, leading to increased expression of S1P1. Taken together, the present study highlights a unique and novel function of CCR2 signaling in the regulation of thymic egress.